RELATIONSHIP BETWEEN FAIR VALUE ACCOUNTING AND FINANCIAL CRISIS OF EUROPEAN BANKING INDUSTRY - Ihda Arifim Faiz; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2015)
Abstract : The study aims to prove a correlation between fair value accounting and the financial crisis in European banking. The use of fair value accounting is considered to exacerbate the financial crisis and is the reason for the re-use of historical cost accounting. By using a logit regression model, this research proves that more fair value-oriented accounting indexes have a weaker relationship with the financial crisis in the banking system than more historically-oriented accounting. However, the grouping of fair value accounting valuation model into three levels creates different strength of the relationship with the financial crisis. The lower the level that is used in an accounting index, the stronger the association between fair value accounting and the financial crisis in the banking system. Moreover, it has been proven that the use of fair value accounting index on liabilities produces a stronger association with the financial crisis in the banking system than when it is used on assets. Abstract The study aims to prove a correlation between fair value accounting and the financial crisis in European banking. The use of fair value accounting is considered to exacerbate the financial crisis and is the reason for the re-use of historical cost accounting. By using a logit regression model, this research proves that more fair value-oriented accounting indexes have a weaker relationship with the financial crisis in the banking system than more historically-oriented accounting. However, the grouping of fair value accounting valuation model into three levels creates different strength of the relationship with the financial crisis. The lower the level that is used in an accounting index, the stronger the association between fair value accounting and the financial crisis in the banking system. Moreover, it has been proven that the use of fair value accounting index on liabilities produces a stronger association with the financial crisis in the banking system than when it is used on assets.